2022
DOI: 10.3390/antiox11030568
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia gmelinii Attenuates Lung Inflammation by Suppressing the NF-κB/MAPK Pathway

Abstract: Cigarette smoke (CS) is the main cause of chronic obstructive pulmonary disease (COPD), and continuous CS exposure causes lung inflammation and deterioration. To investigate the protective effects of Artemisia gmelinii against lung inflammation in this study, cigarette smoke extract (CSE)/lipopolysaccharide (LPS)-treated alveolar macrophages (AMs) and mice stimulated with CSE/porcine pancreas elastase (PPE) were used. Artemisia gmelinii ethanol extract (AGE) was effective in decreasing the levels of cytokines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Artemisia gmelinii Weber ex Stechm (AG) contains various bioactive compounds such as flavonoids, terpenoids, coumarins, caffeoylquinic acids, sterols, and acetylenes. In an earlier study, we demonstrated the beneficial effects of AGE in a respiratory disease model for COPD and allergic airway inflammation [ 20 , 41 ]. Additionally, the present study suggests that AGE effectively inhibits PM-induced lung damage and pulmonary inflammatory responses by suppressing the NF-κB/MAPK pathway and neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisia gmelinii Weber ex Stechm (AG) contains various bioactive compounds such as flavonoids, terpenoids, coumarins, caffeoylquinic acids, sterols, and acetylenes. In an earlier study, we demonstrated the beneficial effects of AGE in a respiratory disease model for COPD and allergic airway inflammation [ 20 , 41 ]. Additionally, the present study suggests that AGE effectively inhibits PM-induced lung damage and pulmonary inflammatory responses by suppressing the NF-κB/MAPK pathway and neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts various biological influences, such as antioxidant, anti-inflammatory, and anti-allergic effects [ 17 , 18 , 19 ]. In addition, our previous study showed that AG ethanol extract (AGE) decreased the release of inflammatory cytokines and chemokines, inhibited MAPK and NF-κB signaling pathways to alleviate lung inflammation in a COPD mouse model, and attenuated inflammation in cigarette smoke extract (CSE)/lipopolysaccharide (LPS)-treated mouse alveolar macrophages (MH-S) [ 20 ]. Nonetheless, the therapeutic effects of AGE on lung inflammation have yet to be demonstrated in a model of PM-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…To set the COPD model, mice were intranasally treated with 20 μL of PPE (1.2 U/head) once a week and CSE (100%) three times a week from days 7 to 18. We decided the dose of PPE/CSE by referring to following references presenting typical COPD symptoms such as airway inflammation, mucus overproduction, and emphysema [ 26 , 27 ]. The COPD and CLE groups were given 200 μL/mouse of PBS or CLE diluted in PBS from days 0 to 18.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of the extracted proteins were measured using the Bradford protein assay. Protein expression was determined by western blot analysis using a previously published method [25,26]. The expression of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) and β-actin (Cell Signaling Technology, USA) in the cytoplasmic fraction, and nuclear factor kappa-light-chain-enhancer of activated B cell (NFκB), p65, and lamin B1 (Cell Signaling Technology) in the nuclear fraction, were measured using the ChemiDoc XRS+ (Bio-Rad, USA).…”
Section: Peritoneal Macrophage Collection and Western Blot Analysismentioning
confidence: 99%
“…COPD was induced using CSE and PPE based on a previously established COPD mouse model [24][25][26]. Oral administration of LLT and LS803 was initiated 7 days before CSE and PPE induction to identify the prophylactic effects.…”
Section: Effect Of Ls803 On Inflammatory Cell Infiltration Cytokines ...mentioning
confidence: 99%